Optimization of nitrogen fertilization improves rice quality by affecting the structure and physicochemical properties of starch at high yield levels - Tian-yang ZHOU; Zhi-kang LI; En-peng LI; Wei-lu WANG; Li-min YUAN; Hao ZHANG; Li-jun LIU; Zhi-qin WANG; Jun-fei GU; Jian-chang YANG (Journal of Integrative Agriculture, 2022)
A major challenge in modern rice production is to achieve the dual goals of high yield and good quality with low environmental costs. This study was designed to determine whether optimized nitrogen (N) fertilization could fulfill these multiple goals. In two-year experiments, two high yielding ‘super’ rice cultivars were grown with different N fertilization management regimes, including zero N input, local farmers’ practice (LFP) with heavy N inputs, and optimized N fertilization (ONF). In ONF, by reducing N input, increasing planting density, and optimizing the ratio of urea application at different stages, N use efficiency and the physicochemical and textural properties of milled rice were improved at higher yield levels. Compared with LFP, yield and partial factor productivity of applied N (PFP) under ONF were increased (on average) by 1.70 and 13.06%, respectively. ONF increased starch and amylose content, and significantly decreased protein content. The contents of the short chains of A chain (degree of polymerization (DP) 6–12) and B1 chain (DP 13–25) of amylopectin were significantly increased under ONF, which resulted in a decrease in the stability of rice starch crystals. ONF increased viscosity values and improved the thermodynamic properties of starch, which resulted in better eating and cooking quality of the rice. Thus, ONF could substantially compensate the negative effects caused by N fertilizer and achieve the multiple goals of higher grain quality and nitrogen use efficiency (NUE) at high yield levels. These results will be useful for applications of high quality rice production at high yield levels.